Perancangan Data Warehouse Menggunakan Model Star Schema untuk Analisis Penjualan Retail Berbasis PostgreSQL - Andri Wijaya; Alexander Novaldi (Journal Of Informatics And Busisnes, 2025)
The retail industry faces significant challenges in managing massive transaction data volumes. Reliance on operational systems (OLTP) often hinders complex historical data analysis. This study aims to design and implement a Data Warehouse using the Star Schema approach to support efficient retail sales analysis. Utilizing the Sample Superstore dataset, the development follows Kimball’s methodology with technical ETL implementation on PostgreSQL. The research produced a Star Schema architecture consisting of one fact table and five dimension tables. Validation testing confirmed complete data integrity during migration. The results demonstrate the system's capability to present rapid multidimensional insights, including positive annual sales trends and profitability disparities across product categories. This implementation proves that PostgreSQL effectively serves as a robust infrastructure for business intelligence, providing a solid foundation for strategic management decision-making.